2010
DOI: 10.1111/j.1748-8583.2010.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Trust as moderator in the relationship between HRM practices and employee attitudes

Abstract: The study contributes to the debate in the HRM literature by examining the role of trust in management in moderating the effect of HRM practices on employee attitudes. The novelty of the study lies in our interest in assessing this relationship not only on a system of HR practices, but also considering whether the influence varies according to specific ‘bundles’ of practices. Adopting a Structural Equation Modelling approach, we first test the moderation using an HRM index of seven practices on a sample of 9,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 49 publications
(69 reference statements)
8
123
0
3
Order By: Relevance
“…Training and Development Armstrong, Flood, Guthrie, Liu, MacCurtain & Mkamwa., 2010;Bainbridge, 2015;Bello-Pintado, 2015;Block & Pickl, 2014;Boon et al, 2014;Boselie et al, 2005;Boselie, 2010;Choi & Yoon, 2015;Choi, 2014;Claudia, 2015;Demortier et al, 2014;Drummond & Stone, 2007;Ehrnrooth & Björkman, 2012;Fu et al, 2013;Ganli, Long, & Ming, 2014;Gould-Williams & Gatenby, 2010;Guerci et al, 2015;Harney & Jordan, 2008;Innocenti et al, 2011;Jiang, Lepak, Hu, et al, 2012;Katou & Budhwar, 2010;Knies & Leisink, 2014;Kroon et al, 2013;Ming et al, 2014;Munteanu, 2014;Obeidat et al, 2010;Raidén et al, 2006;Ramsay, Scholarios & Harley, 2000;Renwick, Redman & Maguire, 2012;Ruzic, 2015;Sarikwal & Gupta, 2013;Schimansky, 2014;Shih et al, 2007;Shin, Jeong & Bae, 2016;Sterling & Boxall, 2013;Tuuli & Rowlinson, 2009;Vermeeren, Kuipers & Steijn, 2014;Wood et al, 2015) Recruitment and Selection ...…”
Section: Ability (A)mentioning
confidence: 99%
See 3 more Smart Citations
“…Training and Development Armstrong, Flood, Guthrie, Liu, MacCurtain & Mkamwa., 2010;Bainbridge, 2015;Bello-Pintado, 2015;Block & Pickl, 2014;Boon et al, 2014;Boselie et al, 2005;Boselie, 2010;Choi & Yoon, 2015;Choi, 2014;Claudia, 2015;Demortier et al, 2014;Drummond & Stone, 2007;Ehrnrooth & Björkman, 2012;Fu et al, 2013;Ganli, Long, & Ming, 2014;Gould-Williams & Gatenby, 2010;Guerci et al, 2015;Harney & Jordan, 2008;Innocenti et al, 2011;Jiang, Lepak, Hu, et al, 2012;Katou & Budhwar, 2010;Knies & Leisink, 2014;Kroon et al, 2013;Ming et al, 2014;Munteanu, 2014;Obeidat et al, 2010;Raidén et al, 2006;Ramsay, Scholarios & Harley, 2000;Renwick, Redman & Maguire, 2012;Ruzic, 2015;Sarikwal & Gupta, 2013;Schimansky, 2014;Shih et al, 2007;Shin, Jeong & Bae, 2016;Sterling & Boxall, 2013;Tuuli & Rowlinson, 2009;Vermeeren, Kuipers & Steijn, 2014;Wood et al, 2015) Recruitment and Selection ...…”
Section: Ability (A)mentioning
confidence: 99%
“…This mystery is popularly known as the "black box" of HRM (Gerhart, 2005;Harney & Jordan, 2008;Innocenti, Pilati & Peluso, 2011). In this respect, Boselie et al (2005) conducted a literature review to analyse the linkages between HRM and performance between 1994 and 2003, and found that many studies acknowledge the existence of the "black box", but few of them tried to look inside it .…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…A convincing interpretation of the relations among HPWS, stress, and satisfaction attributes a mediator effect to the degree of trust in relations between workers and management (Appelbaum et al, 2000;Innocenti et al, 2011). The research by Appelbaum et al (2000) investigated the effects of HPWS on the job satisfaction (one item) and the job stress (three items) of around 4,000 American workers.…”
Section: Stress and Satisfactionmentioning
confidence: 99%